FAKTOR-FAKTOR PENENTU KEPUASAN MAHASISWA TERHADAP PELAYANAN FAKULTAS SEBAGAI LEMBAGA PENDIDIKAN (Studi Kasus di FMIPA, Universitas Udayana) - I Gusti Ayu Made Srinadi & Desak Putu Eka Nilakusmawati (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractThe success of a faculty as a work unit in a university is determined by thequality of the given services than can be measured by the satisfaction of thestudents as its customers. The measurement of the service quality is an importantelement to provide better, more efficient and more effective services. This studyaims to investigate: (1) determinant factors of the students satisfaction of theservices in FMIPA Universitas Udayana; and (2) the dominant factor and itscharacteristics. The data were collected through a questionnaire administered to160 students of FMIPA Universitas Udayana to investigate their perceptions of thefacultys services. The data were analyzed using the descriptive technique and theconfirmatory factor analysis. The results show that, by percentage, no indicator isin the very good category, only one indicator is in the good category, 9 indicatorsare in the fairly good category, and 14 indicators are in the poor category. Theresults indicate that the facultys service quality needs improving. The results of thefactor analysis show that five determinant factors of the students satisfactioninclude tangibles, reliability, responsiveness, assurance, and empathy. By thepriority scale, the reliability factor should be improved first because it is dominantin determining the students satisfaction. Quality indicators constituting thereliability factor include (1) staffs/employees professionalism; (2) employeessociability; (3) comfortable services; (4) staffs politeness; (5) clarity of theinformation given by the staff; and (6) accuracy of the grades in grade cards.Keywords: quality of service, descriptive technique, confirmatory factor analysis,reliability